The forgotten waltz [large type] - Enright, Anne, 1962- (Thorndike Press large print basic series., 2011)
In Terenure, a pleasant suburb of Dublin, it's snowing. Gina Moynihan, girl about town, recalls the trail of lust and happenstance that brought her to fall for "the love of her life," Séan Vallely. Gina remembers their affair: long afternoons made blank by bliss and denial. Now, as the falling snow makes the day luminous and full of possibility, Gina awaits the arrival of Séan's fragile twelve-year-old daughter - the complication, and gravity, of this second life.